Impact of Life History on Fear Memory and Extinction - Remmes, Jasmin; Bodden, Carina; Richter, S. Helene; Lesting, Jörg; Sachser, Norbert; Pape, Hans-Christian; Seidenbecher, Thomas (Frontiers in Behavioral Neuroscience, 2016)
Behavioral profiles are strongly shaped by an individual’s whole life experience. The accumulation of negative experiences over lifetime is thought to promote anxiety-like behavior in adulthood (‘allostatic load hypothesis’). In contrast, the ‘mismatch hypothesis’ of psychiatric disease suggests that high levels of anxiety-like behavior are the result of a discrepancy between early and late environment. The aim of the present study was to investigate how different life histories shape the expression of anxiety-like behavior and modulate fear memory. In addition, we aimed to clarify which of the two hypotheses can better explain the modulation of anxiety and fear. For this purpose, male mice grew up under either adverse or beneficial conditions during early phase of life. In adulthood they were further subdivided in groups that either matched or mismatched the condition experienced before, resulting in four different life histories. The main results were: (i) Early life benefit followed by late life adversity caused decreased levels of anxiety-like behavior. (ii) Accumulation of adversity throughout life history led to impaired fear extinction learning. Late life adversity as compared to late life benefit mainly affected extinction training, while early life adversity as compared to early life benefit interfered with extinction recall. Concerning anxiety-like behavior, the results do neither support the allostatic load nor the mismatch hypothesis, but rather indicate an anxiolytic effect of a mismatched early beneficial and later adverse life history. In contrast, fear memory was strongly affected by the accumulation of adverse experiences over the lifetime, therefore supporting allostatic load hypothesis. In summary, this study highlights that anxiety-like behavior and fear memory are differently affected by specific combinations of adverse or beneficial events experienced throughout life.